2017
DOI: 10.1016/j.polymer.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a microporous 6FDA-polyimide made from a novel carbocyclic pseudo Tröger's base diamine: Effect of bicyclic bridge on gas transport properties

Abstract: Synthesis and characterization of a microporous 6FDA-polyimide made from a novel carbocyclic pseudo Tröger's base diamine: Effect of bicyclic bridge on gas transport properties,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 48 publications
4
30
0
Order By: Relevance
“…In particular, the decomposition temperature values for iPEEK-SBI (T d,5% ¼ 495 C) and iPEEK-Trip (T d,5% ¼ 526 C) were comparable with the commercial PEEK (T d,5% ¼ 550 C), while iPEEK-TB (T d,5% ¼ 405 C) showed a moderate decrease due to the early decomposition of the Tröger's base bridge. 31 The glass transition temperatures (T g ) of the polymers, obtained by differential scanning calorimetry (DSC), were signicantly higher than that of the conventional PEEK (T g ¼ 143 C). For instance, iPEEK-Trip displayed the highest T g of 256 C, followed by iPEEK-SBI of 243 C, and iPEEK-TB of 197 C (Fig.…”
Section: Molecular Design and Synthesismentioning
confidence: 99%
“…In particular, the decomposition temperature values for iPEEK-SBI (T d,5% ¼ 495 C) and iPEEK-Trip (T d,5% ¼ 526 C) were comparable with the commercial PEEK (T d,5% ¼ 550 C), while iPEEK-TB (T d,5% ¼ 405 C) showed a moderate decrease due to the early decomposition of the Tröger's base bridge. 31 The glass transition temperatures (T g ) of the polymers, obtained by differential scanning calorimetry (DSC), were signicantly higher than that of the conventional PEEK (T g ¼ 143 C). For instance, iPEEK-Trip displayed the highest T g of 256 C, followed by iPEEK-SBI of 243 C, and iPEEK-TB of 197 C (Fig.…”
Section: Molecular Design and Synthesismentioning
confidence: 99%
“…MMMs consist of llers with porous structures in a polymeric matrix, including rubber polymers and glassy polymers. Normally, glassy polymers such as polysulfone [15,16], cellulose [17,18], and polyimide [19][20][21] can nicely separate well gas. Of these, polyimide (PI) with highly thermal stability, good chemical stability, and strong mechanical stability has been extensively used as gas separation membrane [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…4 The most commonly used dianhydride monomers in the preparation of polyimides for gas separation membranes are 4,4 0 -(hexauoroisopropylidene)diphthalic anhydride (6FDA), pyromellitic dianhydride (PMDA) and 4,4 0 -oxidiphthalic anhydride (ODPA). [5][6][7][8][9][10] Nevertheless, the synthesis of new dianhydrides is a subject of considerable current interest since they allow the design and synthesis of novel polyimides for gas separation membranes. In this regard, Ma et al reported two novel carbocyclic pseudo-Tröger's derived dianhydrides, which were employed to prepare soluble polyimides with an excellent gas separation performance, exceeding the upper bound for O 2 /N 2 , and H 2 /CH 4 .…”
Section: Introductionmentioning
confidence: 99%